Loss of ATE1-mediated arginylation leads to impaired platelet myosin phosphorylation, clot retraction, and in vivo thrombosis formation - Lian, Lurong (Ferrata Storti Foundation, 2014)
Protein arginylation by arginyl–transfer RNA protein transferase (ATE1) is emerging as a regulator protein function that is reminiscent of phosphorylation. For example, arginylation of β-actin has been found to regulate lamellipodial formation at the leading edge in fibroblasts. This finding suggests that similar functions of β-actin in other cell types may also require arginylation. Here, we have tested the hypothesis that ATE1 regulates the cytoskeletal dynamics essential for in vivo platelet adhesion and thrombus formation. To test this hypothesis, we generated conditional knockout mice specifically lacking ATE1 in their platelets and in their megakaryocytes and analyzed the role of arginylation during platelet activation. Surprisingly, rather than finding an impairment of the actin cytoskeleton structure and its rearrangement during platelet activation, we observed that the platelet-specific ATE1 knockout led to enhanced clot retraction and in vivo thrombus formation. This effect might be regulated by myosin II contractility since it was accompanied by enhanced phosphorylation of the myosin regulatory light chain on Ser19, which is an event that activates myosin in vivo. Furthermore, ATE1 and myosin co-immunoprecipitate from platelet lysates. This finding suggests that these proteins directly interact within platelets. These results provide the first evidence that arginylation is involved in phosphorylation-dependent protein regulation, and that arginylation affects myosin function in platelets during clot retraction.